Pengaruh Fleksibilitas Operasional dan Kualitas Teknologi Informasi Kesehatan terhadap Kinerja Rumah Sakit yang Dimediasi oleh Kapabilitas Manajemen di RSUD Arifin Achmad Riau - Anggarawati, Wiwik Suryandartiwi; Zaky, Abdul; Handoko, Bobi (LPPM Hang Tuah Pekanbaru, 2025)
The obligation of hospitals to provide safe and quality health services causes every hospital to improve the quality of its services. Arifin Achmad Riau Hospital as a Type A Hospital has several problems such as lack of Management Capability to optimize the skills of officers in doing work, lack of Operational Flexibility related to response ability to simplify work processes and lack of ability to develop Quality of health information technology to support the process of accelerating health services. The type of research is quantitative with a causal approach. The sample determination method uses the Purposive Sampling technique so that the number of samples is 84 staff of Arifin Achmad Riau Hospital. Data collection method with questionnaire and data analysis techniques through Struktural Equation Modelling analysis. The quality of health information technology has a major impact on management capability, while operational flexibility has little bearing on it. Operational Flexibility and Quality of Health Information Technology do not have a significant effect on Hospital performance, but Management capability has a significant effect on Hospital performance, Management capability is able to reduce the relationship between Quality of Health Information Technology and Hospital performance, but Management capability is able to reduce The relationship between Operational Flexibility and Hospital performance. To improve hospital performance, it is necessary to pay attention to the factors of Fleksibilitas Operasional, Quality of Health Information Technology and Management Capability.